2004
DOI: 10.1080/01443610400019005
|View full text |Cite
|
Sign up to set email alerts
|

Microwave endometrial ablation for menorrhagia: outcome at 2 years--experience of a district general hospital

Abstract: One hundred and twenty-three women underwent microwave endometrial ablation (MEA) for the treatment of dysfunctional uterine bleeding (DUB). The mean age at treatment was 40.2 years and the average treatment time was 2 minutes 50 seconds. All patients stayed as day cases, except for two who stayed overnight, one due to pain and the other due to urinary retention. The follow-up was carried out at 6 months, 1 and 2 years, respectively. The success rate was 80%, 76% and 70% at 6 months and 1-year and 2-year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 3 publications
3
14
2
Order By: Relevance
“…She would return in several months or years time because of treatment failure. Such women ultimately would have a hysterectomy after prolonged periods of dissatisfaction (Sharma et al 2004;Kuzel et al 1999;McCausland and McCausland 1998). Timely confident diagnosis of adenomyosis can avoid unnecessary interventions and procrastination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…She would return in several months or years time because of treatment failure. Such women ultimately would have a hysterectomy after prolonged periods of dissatisfaction (Sharma et al 2004;Kuzel et al 1999;McCausland and McCausland 1998). Timely confident diagnosis of adenomyosis can avoid unnecessary interventions and procrastination.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical diagnosis of adenomyosis is important for patient counselling as regards provision of management options. For example, endometrial ablation is not very effective in the management of menorrhagia secondary to deep-seated adenomyosis (Reinhold et al 1999;Sharma et al 2004;Kuzel et al 1999). …”
Section: Introductionmentioning
confidence: 95%
“…This is supported by the fact that for five patients with pain pre-MEA who were not cured by hysteroscopic adhesiolysis, pathological study revealed two had endometriosis and three had adenomyosis, for which hysteroscopic adhesiolysis would not be the treatment of choice. Other similar studies confirm that the majority of patients undergoing hysterectomy, for continued bleeding or pain, following endometrial ablation have other pathology present such as adenomyosis or endometriosis [2,11].…”
Section: Discussionmentioning
confidence: 87%
“…It has been granted National Institute of Clinical Excellence approval and has been shown to be effective in 70-80% of women [1]. The overall risk of complications associated with MEA is small [1,2], although long term data on complications and success rates is lacking. One complication that has been associated with first generation endometrial ablative techniques is postoperative pelvic pain.…”
Section: Introductionmentioning
confidence: 99%
“…4 The incidence of pregnancy after ablative techniques is as low as 0.7%. 2 In 2006, 74 pregnancies were reported after endometrial ablative methods.…”
Section: Discussionmentioning
confidence: 99%